2006
DOI: 10.1111/j.1365-2958.2006.05395.x
|View full text |Cite
|
Sign up to set email alerts
|

The carrier Msn5p/Kap142p promotes nuclear export of the hsp70 Ssa4p and relocates in response to stress

Abstract: SummaryCytoplasmic hsp70s like yeast Ssa4p shuttle between nucleus and cytoplasm under normal growth conditions but accumulate in nuclei upon stress. This nuclear accumulation is only transient, and Ssa4p relocates to the cytoplasm when cells recover. We show here that Ssa4p nuclear export is independent of Xpol/Crm1 and identify the importin-b family member Msn5p/Kap142p as the exporter for Ssa4p. In growing cells and in vitro, Msn5p and Ssa4p generate genuine export complexes that require Ran/Gsp1p-GTP. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…It was shown that whenever Msn5 was detected in the cytoplasm, Saa4 protein, another Msn5 cargo, was concentrated in the nucleus (16). It was suggested that when Msn5 was sequestered in the cytoplasm, it was unable to ferry its cargo from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that whenever Msn5 was detected in the cytoplasm, Saa4 protein, another Msn5 cargo, was concentrated in the nucleus (16). It was suggested that when Msn5 was sequestered in the cytoplasm, it was unable to ferry its cargo from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the Msn5 carrier, nuclearly localized under standard conditions in glucose, becomes redistributed to the cytoplasm upon transfer to a medium with a nonfermentable carbon source (16). It was shown that whenever Msn5 was detected in the cytoplasm, Saa4 protein, another Msn5 cargo, was concentrated in the nucleus (16).…”
Section: Discussionmentioning
confidence: 99%
“…Like other ␤-karyopherin export receptors including the nuclear tRNA export receptor Los1p, loading of Msn5p with protein cargo has been shown to be dependent on the Ran GTPase Gsp1p in the GTP bound form (Hellmuth et al, 1998;Quan et al, 2006). Consequently, protein-binding studies were conducted in vitro to ascertain whether the interaction between Msn5p and tRNA is dependent on Gsp1p-GTP ( Figure 14B).…”
Section: ) and This Notion Is Consistent With In Vitro And In VImentioning
confidence: 99%
“…Msn5p can import or export different proteins and RNAs. Export from the nucleus of the transcription factors Pho4p (Kaffman et al, 1998), Mig1p (DeVit andJohnston, 1999), Msn2p-Msn4p (Gorner et al, 2002), Crz1 (Boustany and Cyert, 2002), Rtg1p-Rtg3p (Komeili et al, 2000), Swi6p (Queralt and Igual, 2003), and other yeast proteins, such as the Cln-Cdc28p inhibitor Far1p (Blondel et al, 1999), the MAPK scaffold protein Ste5 (Mahanty et al, 1999), the chaperone hsp70-Ssa4p (Quan et al, 2006), and the Ho endonuclease (Bakhrat et al, 2008), has been shown to be mediated by Msn5p. In addition, the mammalian Exportin-5 mediates nuclear export of pre-miRNAs (Bohnsack et al, 2004), and Msn5p can also bind short noncoding double-stranded RNAs (Shibata et al, 2006).…”
Section: Discussionmentioning
confidence: 99%